A computational model of first language acquisition - Satake, Nobuo. (Series in computer science, 1990)
Introduction; Phenomena in language acquisition and primary data; Learnability theory; BUD and other computational models; The whole constitution of BUD; BUD's category-formation/Integration/Disruption mechanism; Comparison between language phenomena and BUD's behavior; Order mode and production mode; Final remarks.